MODEL KONSELING KELOMPOK COGNITIVE BEHAVIOR UNTUK MENINGKATKAN SELF ESTEEM SISWA SMK - Habsy, Bakhrudin All (Perspektif Ilmu Pendidikan, 2017)
The purpose of this research is to test effectiveness of Cognitive Behavior Group Counseling to increase self esteem of vocational high school students. The research was conducted from November to January 2016. In this research, a researcher used exsperiment structure with design pretest and posttest control group. Grounded on result of measure inventory self esteem issues twelve students identification as students have characteristic low self esteem. Furthermore comb out subject for group experiment and group control used by random with amount six students for every group. There are two kinds of instrument are used those are instument treatment and measure. Instrument treatment as project implementation group counseling cognitive behavior, whereas instrument measure as inventory self esteem which has validity value grain total with value R on top of 0,32, and realibility are 0,945 can be concluded inventory self esteem reliable and worth as a research instrument. The data is analyzed with test statistic nonparametrik Two Independent Sample Test Mann Whitney U. The income hypothesis get value Z is -2,242 and figure Asymp. Sig. (2-tailed) is 0,025 < 0,05, so Ho is refused, which meaning effectiveness of Cognitive Behavior Group Counseling to increase self esteem of Vocational high school. Based on the analysis of the found the research (1) to counselor: Cognitive Behavior Group Counseling can be carried out to increase self esteem of vocational high school students, and can be principle to understanding of grown students; and 2) to next researcher: This research applicate Cognitive Behavior Group Counseling with cognitive restructuring, problem solving and homework technique, for the Next researcher can test the effectiveness by using the other technique that relevant, or may be the researcher can use the other design as single subject design, action research in guidence and counseling, or the other exsperiment research that model Cognitive Behavior Group Counseling can be test the effectiviness.